Digital First Primary Care: Medicolegal issues. (2nd March 2020) - Mounsey, Heidi
Abstract : Mounting pressures on NHS services have made digital solutions inevitable, and NHS England expects all primary care patients to have the right to online consultations by April 2020 – but with new technology comes new risks, says Heidi Mounsey